MODERN ASPECTS OF THE PATHOGENESIS OF COMORBIDITY IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Juraeva Firuza Raxmatovna (Scholar Express Journals, 2022)
This review article presents modern aspects of the pathogenetic mechanisms of the formation of bronchial obstruction and pulmonary emphysema in chronic obstructive pulmonary disease occurring against the background of comorbid diseases. The author summarizes the latest research on the interaction of cardio-respiratory pathologies and prevention of complications of these conditions
Keywords: Chronic Obstructive Pulmonary Disease; Comorbid Pathology; Prognosis; Respiratory System